CRIMINAL LAW OF THE ENEMY - Suárez Pérez, Néstor (2023)
In the present essay I question the essential foundations of the criminal law of the enemy, such as the expulsion of the potentially dangerous individual to a natural factual state, the lack of consideration of the existence of more than one kind of social contract, the absence of analysis of the potentially unlawful inclination through a cognitive structure of the enemy, and punishment as a legal mechanism of appearances.